Synthesis of PVA-based macromolecular photoinitiators through esterification with TXOCH2COOH and cysteine, and investigation of their photophysical properties: in situ fabrication of flexible nanocomposite films - Konar, Melisa; Nakamura, Kazuki; Arsu, Nergis (FRONTIERS MEDIA SA, 2025)
2-(Carboxymethoxy) thioxanthone (TX-OCH2COOH), a thioxanthone derivative, was utilized for the esterification of polyvinyl alcohol (PVA) to synthesize a macromolecular photoinitiator, both in the absence and presence of Cysteine (Cys). The covalent attachment of the thioxanthone (TX) group to PVA through esterification enabled the exploration of the photophysical properties of the resulting macromolecular photoinitiators (TXOCH2COO-PVA and TXOCH2COO-PVA-Cys) via UV-Vis and fluorescence studies. UV-Vis absorption spectrum of TXOCH2COO-PVA confirmed the covalent bonding of TX, marked by a characteristic absorption peak at 397 nm corresponding to the thioxanthone chromophore. Fluorescence lifetimes were recorded as TXOCH2COO-PVA was cast into a mold and air dried, resulting in a flexible form of PVA esterified with TXOCH2COOH. In-situ synthesis of both silver and selenium nanoparticles was carried out using both TXOCH2COO-PVA and TXOCH2COO-PVA-Cys macromolecular initiators, successfully yielding nanocomposite flexible polymeric films.
Keywords: photoinitiator; flexible polymeric films; thioxanthones (TX); polyvinyl alcohol (PVA); esterification reaction; silver nanoparticles (AgNPs); POLY(VINYL ALCOHOL); PHOTOPOLYMERIZATION; THIOXANTHONE; HYDROGEL; OXIDE; ACID; BIOCOMPATIBILITY; POLYMERIZATION; NANOPARTICLES; POLYMERS; Materials Science